2011
DOI: 10.1587/transinf.e94.d.2495
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Pitch Patterns in Japanese Speakers of English with Verification by Speech Re-Synthesis

Abstract: SUMMARYCertain irregularities in the utterances of words or phrases often occur in English spoken by Japanese native subject, referred to in this article as Japanese English. Japanese English is linguistically presumed to reflect the phonetic characteristics of Japanese. We consider the prosodic feature patterns as one of the most common causes of irregularities in Japanese English, and that Japanese English would have better prosodic patterns if its particular characteristics were modified. This study investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Then, we found that Japanese English had the features that nouns and adjectives were ''ntv>jpe,'' and adverbs and verbs were ''ntv<jpe.'' The results in our previous study [13] corroborate the results in subsection 4.2.1.…”
Section: Summary Of the Results In Subsections 42 And 43supporting
confidence: 91%
See 1 more Smart Citation
“…Then, we found that Japanese English had the features that nouns and adjectives were ''ntv>jpe,'' and adverbs and verbs were ''ntv<jpe.'' The results in our previous study [13] corroborate the results in subsection 4.2.1.…”
Section: Summary Of the Results In Subsections 42 And 43supporting
confidence: 91%
“…In our previous study [13], the pitch in Japanese English was analyzed, and the result was checked by the speech synthesis. Then, we found that Japanese English had the features that nouns and adjectives were ''ntv>jpe,'' and adverbs and verbs were ''ntv<jpe.''…”
Section: Summary Of the Results In Subsections 42 And 43mentioning
confidence: 99%